Opportunistic yeast pathogen Candida spp.: secreted and membrane-bound virulence factors - Si, Jie Lim; Mohamad Ali, Mohd Shukuri; Sabri, Suriana; Muhd Noor, Noor Dina; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Oxford University Press, 2021)
Candidiasis is a fungal infection caused by Candida spp. especially Candida albicans, C. glabrata, C. parapsilosis and C. tropicalis. Although the medicinal therapeutic strategies have rapidly improved, the mortality rate as candidiasis has continuously increased. The secreted and membrane-bound virulence factors (VFs) are responsible for fungal invasion, damage and translocation through the host enterocytes besides the evasion from host immune system. VFs such as agglutinin-like sequences (Als), heat shock protein 70, phospholipases, secreted aspartyl proteinases (Sap), lipases, enolases and phytases are mostly hydrolases which degrade or interact with the enterocyte membrane components. Candidalysin, however, acts as a peptide toxin to induce necrotic cell lysis. To date, structural studies of the VFs remain underexplored, hindering their functional analyses. Among the VFs, only Sap and Als have their structures deposited in Protein Data Bank (PDB). Therefore, this review scrutinizes the mechanisms of these VFs by discussing the VF-deficient studies of several Candida spp. and their abilities to produce these VFs. Nonetheless, their latest reported sequential and structural analyses are discussed to impart a wider perception of the host-pathogen interactions and potential vaccine or antifungal drug targets. This review signifies that more VFs structural investigations and mining in the emerging Candida spp. are required to decipher their pathogenicity and virulence mechanisms compared to the prominent C. albicans.